PEMBUATAN ALAT PERAGA SEDERHANA UNTUK MEMAHAMI SIFAT-SIFAT CAHAYA BAGI KELOMPOK ANAK SEKOLAH DASAR DI SENTANI KABUPATEN JAYAPURA - Radjabaycolle, Flinn; Bungkang, Yusuf; Bunga, Martina; Soll, Melfi (LPPM Uncen, 2024)
Children who live in Perumahan BTN Puskopad Jalur 7 Bawah Sentani, Kabupaten Jayapura, experience difficulties learning physics. One of the factors causing this is the lack of sufficient support from the school environment and family. Parents hand over all teaching responsibilities to teachers, while teachers at school cannot teach optimally. Teachers only depend on textbooks, and children are forced to memorize lesson material according to what is written in the book. Children are also unable to carry out practical work as they should because of inadequate laboratory equipment. This style of learning makes it difficult for children to understand physics well. To learn physics, children need concrete scientific experience. Based on this background, the community service team held activities by making simple teaching aids related to the subject matter of light. Children are expected to be able to understand the properties of light, namely that it can travel in a straight line, can penetrate transparent surfaces of objects, can be reflected, and can be refracted. Apart from that, it is also hoped that children will be interested in physics lessons through this activity. This service is carried out using experimental methods with tools and materials that are easily found in everyday life. The benefit of this service is that it provides knowledge for children when studying the properties of light in science subjects at formal schools. The results achieved from this service activity show that the service participants understand the properties of ligh t, are satisfied and happy while carrying out light experiments, and as many as 75% of children are interested in studying physics.